Choosing cyber during COVID. (September 2021) - Maranto, Robert; Beck, Dennis; Clark, Tom; Tran, Bich; Liu, Feng
Substantial research has already examined how the COVID-19 pandemic has affected in-person schooling, but no prior work has explored its effects on cyber schools. Here, Robert Maranto, Dennis Beck, Tom Clark, Bich Tran, and Feng Liu compare the students entering a large national cyber charter school network in spring 2020, during the pandemic, with students entering in 2019 and 2018, before the pandemic. They find that the COVID cohort resembled prior groups demographically but reported greater success at their prior in-person schools and exhibited greater measured success in cyber schools .